Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Keterampilan Proses Sains pada Materi Sistem Regulasi - Damayanti, Norma; Permadani, Karunia Galih; Sukmawati, Ika (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2023)
This research is motivated by the students' scientific process skills that are not optimal, the student worksheet is not in accordance with the needs, and on the material of the regulatory system practicum activities have not been carried out. This study aims to develop and produce products in the form of student worksheet based on science process skills that are valid, practical, and can improve the ability of students' science process skills. The research method used is Research and Development (R&D) with a 4D development model. However, in this study only up to the third stage, namely Develop. This research was tested by pre-experiment by one group pretest-posttest design. Collecting data using interviews, questionnaires, and tests. The data analysis technique used descriptive qualitative analysis. The results of this study indicate that the student woksheet developed is feasible to use. The percentage level of validity obtained is 88.625% (very valid) and the practicality level is 92.5% (very practical). The results of the N-Gain trial obtained an average N-Gain of 0.5709 (medium) and a percentage of 57.09% (quite effective). It was concluded that the student worksheet developed was suitable for use in learning activities. and can improve students' science process skills.